The SUMO-Conjugase Ubc9 Prevents the Degradation of the Dopamine Transporter, Enhancing Its Cell Surface Level and Dopamine Uptake - Cartier, Etienne; Garcia-Olivares, Jennie; Janezic, Eric; Viana, Juan; Moore, Michael; Lin, Min Landon; Caplan, Jeffrey L.; Torres, Gonzalo; Kim, Yong-Hwan (Frontiers in Cellular Neuroscience, 2019)
The dopamine transporter (DAT) is a plasma membrane protein responsible for the uptake of released dopamine back to the presynaptic terminal and ending dopamine neurotransmission. The DAT is the molecular target for cocaine and amphetamine as well as a number of pathological conditions including autism spectrum disorders, attention-deficit hyperactivity disorder (ADHD), dopamine transporter deficiency syndrome (DTDS), and Parkinson’s disease. The DAT uptake capacity is dependent on its level in the plasma membrane. In vitro studies show that DAT functional expression is regulated by a balance of endocytosis, recycling, and lysosomal degradation. However, recent reports suggest that DAT regulation by endocytosis in neurons is less significant than previously reported. Therefore, additional mechanisms appear to determine DAT steady-state level and functional expression in the neuronal plasma membrane. Here, we hypothesize that the ubiquitin-like protein small ubiquitin-like modifier 1 (SUMO1) increases the DAT steady-state level in the plasma membrane. In confocal microscopy, fluorescent resonance energy transfer (FRET), and Western blot analyses, we demonstrate that DAT is associated with SUMO1 in the rat dopaminergic N27 and DAT overexpressing Human Embryonic Kidney cells (HEK)-293 cells. The overexpression of SUMO1 and the Ubc9 SUMO-conjugase induces DAT SUMOylation, reduces DAT ubiquitination and degradation, enhancing DAT steady-state level. In addition, the Ubc9 knock-down by interference RNA (RNAi) increases DAT degradation and reduces DAT steady-state level. Remarkably, the Ubc9-mediated SUMOylation increases the expression of DAT in the plasma membrane and dopamine uptake capacity. Our results strongly suggest that SUMOylation is a novel mechanism that plays a central role in regulating DAT proteostasis, dopamine uptake, and dopamine signaling in neurons. For that reason, the SUMO pathway including SUMO1, SUMO2, Ubc9, and DAT SUMOylation, can be critical therapeutic targets in regulating DAT stability and dopamine clearance in health and pathological states.